Дублиндік дескриптор негізінде оқыту нəтижесін бағалау - Бұзаубақова, К.Ж. (My University, 2016)
In this article is opened the methodic of evaluation of result of teaching on a base of Dublin descriptor managing some basic principles of content of education which are directed on the competence approach.
Keywords: Competence; Dublin descriptor; Smart- aim; competence diagram